Pulmonary vascular remodeling occurs in severe equine asthma. (International Journal of Health, Animal Science and Food Safety, 2016)
Severe equine asthma (heaves) is a chronic genetic-environmental condition characterized by airwayneutrophilic inflammation leading to airway obstruction, lung tissue remodeling and hypoxemia(Bullone, 2015). Hypoxemia triggers pulmonary vasoconstriction, resulting in higher vascular resistanceand development of pulmonary hypertension (PH). PH-associated cardiovascular complications couldbe present in the end-stage disease, as it happens in human type 3 PH (Tsangaris, 2012). Pulmonaryvascular remodeling is involved in the pathogenesis of type 3 PH (Singh, 2016) and may represent atherapeutic target for preventing PH onset, both in human and in horses. In this study, we investigatedthe presence of pulmonary artery remodeling in severe equine asthma, as, to the best of our knowledge,this has not been yet studied. Lung biopsy specimens were collected via thoracoscopy from 6 asthmaticand 5 age-matched control horses. Histomorphometric assessment was performed on Movat-Russellstained histological sections, evaluating pulmonary artery wall area, intimal area, medial area and theircorrelations with the internal elastic lamina length (IEL) (Fernie, 1985). The total amount of smoothmuscle within the artery wall and the density of proliferating smooth muscle cells were similarlyevaluated using immunostaining for α-smooth muscle actin (α-SMA) and proliferating cell-associatednuclear antigen (PCNA). Increased pulmonary wall area, increased amount of smooth muscle and lossof correlation between intimal area and IEL were present in asthmatic horses, when compared tocontrols. In conclusion, pulmonary artery remodeling due to smooth muscle hypertrophy and intimalmuscolarization may be induced by persistence of hypoxic vasoconstriction stimulus and release ofcytokines from inflammatory cells infiltrating the annexed airways (Barbera, 2003).
Keywords: Equine asthma; pulmonary vascular remodeling; pulmonary hypertension; histomorphometry